Self-Preparedness and Motivation to Perform Clinical Practice During the Covid-19 Pandemic among Nursing Students - Eldamai Purnamasari Sarumaha; Eve Ivana Priscila Dawa; Tesya Marcellyta Gansalangi; Juhdeliena Juhdeliena; Gracia Aktri Margareth Manihuruk (Jurnal Keperawatan, 2022)
COVID-19 pandemic has an impact on the field of education, especially nursing. Nursing students cannot perform nursing care directly to the patients because learning activities are conducted online. As many as 33 out of 40 students (82.5%) said they were afraid to practice in clinical setting. This study aimed to identify self-preparedness and motivation to perform clinical practice during the COVID-19 pandemic. This study used a quantitative descriptive research method with a sample of 153 respondents, using a modified questionnaire from previous research and distributed online. Researchers used univariate data analysis. Respondents who have good self-preparedness to participate in clinical practice totaled 81 respondents (52.9%), and those who have good motivation to perform clinical practice amounted to 77 respondents (50.3%).The majority of respondents have good self-preparedness and good motivation to participate in clinical practice, but there are still students who have good self-preparedness with lack of motivation to participate in clinical practice during the COVID-19 pandemic. Students are suggested to be able to further improve their preparedness and motivation before participating in clinical practice.